Role-Playing Technique for Improving Students Speaking Ability in the Simple Past Tense - Ni Putu Lindawati; Ni Komang Purwaningsih; Si Putu Agung Ayu Pertiwi Dewi (English Language in Focus (ELIF), 2021)
This research aimed to find out how far the use of role-play technique could help the students of Triatma Jaya Badung Vocational High School in grade XI Hospitality Accommodation 1 to improve their speaking ability especially in using the simple past tense. Some theoretical frameworks are used in this research, such as the theory of teaching speaking by Richard and the theory of teaching grammar by Williams. Before the treatment was carried, a pretest was conducted to know the students’ basic ability, so that the achievement can be compared with the next circles after the treatment was given. The result of quantitative data showed that the use of role-play technique could improve the speaking ability of students of Triatma Jaya Badung Vocational High School. It can be seen from the result of the students’ achievement tests which increased continuously during the application of the role play technique. Those speaking aspects which were used as an indicator are vocabulary, pronunciation, grammar, fluency, and comprehension.